2018
DOI: 10.1021/acschembio.8b00914
|View full text |Cite
|
Sign up to set email alerts
|

NMR Dynamics Study Reveals the Zα Domain of Human ADAR1 Associates with and Dissociates from Z-RNA More Slowly than Z-DNA

Abstract: Human RNA editing enzyme ADAR1 deaminates adenosine in pre-mRNA to yield inosine. The Zα domain of human ADAR1 (hZαADAR1) binds specifically to left-handed Z-RNA as well as Z-DNA and stabilizes the Z-conformation. To answer the question of how hZαADAR1 can induce both the B–Z transition of DNA and the A–Z transition of RNA, we investigated the structure and dynamics of hZαADAR1 in complex with 6-base-pair Z-DNA or Z-RNA. We performed chemical shift perturbation and relaxation dispersion experiments on hZαADAR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…These observations led us to question whether Z-DNA states influence the threshold for experience-dependent transcriptional activity, which itself is critical for at least the first stage of memory consolidation 12 . Given that Adar1 recognizes Z-DNA in vitro 13 , and potentially alters the formation of Z-DNA 14 , 15 , we hypothesized that Adar1-mediated changes in DNA structure states are critical for learning-induced gene expression in the adult brain and that this impacts the formation of fear extinction memory, an important form of memory that is dependent on rapid changes in gene expression 16 and on behavioral flexibility following extinction learning 17 . In confirmation of this hypothesis we observed that Z-DNA is dynamic in response to fear extinction learning, with manipulation of Z-DNA by doxorubicin impairing extinction when infused into the infralimbic PFC.…”
Section: Introductionmentioning
confidence: 99%
“…These observations led us to question whether Z-DNA states influence the threshold for experience-dependent transcriptional activity, which itself is critical for at least the first stage of memory consolidation 12 . Given that Adar1 recognizes Z-DNA in vitro 13 , and potentially alters the formation of Z-DNA 14 , 15 , we hypothesized that Adar1-mediated changes in DNA structure states are critical for learning-induced gene expression in the adult brain and that this impacts the formation of fear extinction memory, an important form of memory that is dependent on rapid changes in gene expression 16 and on behavioral flexibility following extinction learning 17 . In confirmation of this hypothesis we observed that Z-DNA is dynamic in response to fear extinction learning, with manipulation of Z-DNA by doxorubicin impairing extinction when infused into the infralimbic PFC.…”
Section: Introductionmentioning
confidence: 99%
“…Recent NMR studies suggested an active mechanism of B-Z transition, which support two independent roles of ZBPs as follows [123,145,[153][154][155]: (i) one ZBP molecule binds to 6-bp B-DNA, d(CG) 3 , and facilitates the conversion from B-DNA to Z-DNA; (ii) the second ZBP forms the complete DNA-(ZBP) 2 complex. The Zα domain of human ADAR1 (hZα ADAR1 ), which stabilizes the Z-DNA conformation, is able to bind to a 6-bp Z-DNA duplex with not only CG-repeat-rich sequences but also non-CG-repeat sequences [156].…”
Section: Z-dna Complexes With Zbpsmentioning
confidence: 96%
“…A kinetic model demonstrated that active-mono B-Z conversion bridged the equilibrium between B-form complex (BP) and Z-form complex (ZP). Recently, Lee et al carried out the structural dynamics analysis of hZα ADAR1 -d(CG) 3 complexes based on the global fitting methods of relaxation dispersion combined with CSP [155]. 15 N CPMG relaxation dispersion results showed that hZα ADAR1 with Z-DNA undergoes a pseudo-three-state conformational exchange, which includes two independent B-Z transitions for the free and bound states.…”
Section: Z-dna Complexes With Zbpsmentioning
confidence: 99%
“…Single-molecule FRET studies reported that Z-conformations are sampled transiently, supporting a conformational capture model ( Bae et al 2011 ). However, other evidence suggests that Z-forming RNAs (and DNAs) adopt multiple intermediate states between the initial binding of a winged helix Zα domain to A- (or B-) form followed by Z formation ( Kang et al 2009 ; Lee et al 2011 , 2016 , 2019 ). Therefore, a hybrid model may be more suitable to explain Z-RNA formation in some cases, wherein an active binding event between Zα and a Z-conformation-forming sequence pushes the nucleic acid into an intermediate state that Zα then locks into the Z-conformation ( Fig.…”
Section: What Did We Learn From Studying Z-rna In Vitro?mentioning
confidence: 99%